SIMBOL DAN MAKNA ADEGAN BERDERMA (DÂNA) PADA RELIEF KARMAWIBHANGGA CANDI BOROBUDUR - Tsanaa Khenresta; Rani Chandra Oktaviani; Yonaz Salasa (Balai Arkeologi Provinsi Sulawesi Selatan, 2022)
This research focus on how to interpretate symbols & meanings of depiction the act of charity that appear on Candi Borobudur’s feets, called as relief of Karmawibhangga. Charity is one of the steps of useful actions, punnakiriyavatthu. Charity originated from Pali’s language, dana. Charity is one of basic positive activity that can be done by everyone, everywhere. This charity acts drawn at candi’s relief. The depiction of this charity acts shown major at the Karmawibhangga’s relief, at least 40 acts of this charity been carved. The distribution of this relief rely on the relief of Karmawibhangga, most widely shown at west – north’s side. The most of depiction the act of charity is food, then a container, something that is unidentified, clothes, jewelry, flower, and umbrella and charity is done by the nobleman, religionist, and common people Penelitian ini berfokus kepada bagaimana intrepretasi simbol dan makna penggambaran adegan berderma yang ada pada kaki Candi Borobudur, relief Karmawibhangga. Analisis yang digunakan adalah teori semiotika dari Roland Barthes. Derma merupakan dasar tingkatan dalam tahapan tindakan bermanfaat, punnakiriyavatthu. Derma merupakan arti kata dana yang berasal dari bahasa Pali. Derma merupakan kegiatan mendasar positif yang bisa dilakukan oleh siapa dan dimana saja. Derma merupakan salah satu adegan yang digambarkan pada relief candi. Penggambaran adegan derma paling banyak ditemui pada relief Karmawibhangga, sebanyak 40 adegan derma dipahatkan. Sebaran relief derma pada relief Karmawibhangga paling banyak dijumpai pada sisi barat –utara. Derma yang paling banyak adalah derma pangan, wadah, sesuatu yang tidak teridentifikasi, sandang, perhiasan, bunga, dan payung. Pemberian derma ini dilakukan oleh ketiga golongan masyarakat yaitu para bangsawan, agamawan, juga orang biasa.